2022
DOI: 10.1101/2022.08.31.506075
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A metabolic sum rule dictates bacterial response to short-chain fatty acid stress

Abstract: Short-chain fatty acids (SCFAs) such as acetate accumulate in fermentative environments, inhibiting many types of bacteria. While it is known that cells accumulate SCFAs to high concentrations internally, the cause of SCFA toxicity is not understood. By forcing Escherichia coli cells to accumulate a variety of "useless metabolites", we establish via extensive 'omic analysis a metabolic sum rule, by which the accumulation of exogenous metabolites such as acetate forces the depletion of endogenous metabolites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Lactate and pyruvate from 1A01 relieves the growth bottleneck of 3B05, allowing it to resume growth and thereby consume acetate, the source of stress. While we have emphasized metabolic interactions in this model, we note that gene regulation would likely also play important roles during the growth recovery process as described in recent studies 46,79 .…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Lactate and pyruvate from 1A01 relieves the growth bottleneck of 3B05, allowing it to resume growth and thereby consume acetate, the source of stress. While we have emphasized metabolic interactions in this model, we note that gene regulation would likely also play important roles during the growth recovery process as described in recent studies 46,79 .…”
Section: Resultsmentioning
confidence: 90%
“…The excreted acids become toxic when the environment becomes acidified, i.e., when pH drops to the level of the acids’ dissociation constants, ∼5 for weak acids such as acetate 44,45 . Under these conditions, the ionic form of the acid builds to high concentrations in the cytoplasm, reducing the pools of key metabolic intermediates due to a osmotic constraint 46 . While the presence of “acid eaters” specializing on acids in non-stress conditions can theoretically prevent acidification, we find that such acid eaters are themselves growth-inhibited when the pH drops.…”
mentioning
confidence: 99%
“…In this work, we have investigated models of growth and survival of microbial species in communities subjected to cyclic environmental fluctuations, focusing on the case of prolonged periods between nutrient replenishment as seen often in the wild [34, 44]; under these conditions, exponential steady-state growth cannot be sustained. In the lab, non-steady-state growth can occur during serial-dilution cycles where the cycle length is long enough for nutrient depletion or build up for toxic waste that limits growth [12, 36, 45]. Accurate bottom-up models are not feasible given our limited understanding of microbial behaviors outside of exponential growth [44, 46].…”
Section: Discussionmentioning
confidence: 99%
“…Amarnath et al [16] showed that this highly dynamical mode of coexistence is not specific to the marine species studied: dynamic coexistence through similar acid shock and recovery was shown also for co-culture of species taken from a soil community or even between enteric and soil bacterium. Metabolic analysis in [16,36] suggests that such interactions are generic between species with complementary sugar-preferring vs. acid-preferring bacteria, or between glycolytically-oriented vs. gluconeogenically-oriented modes of metabolism. Thus, dynamic coexistence with each species passing through multiple physiological states in a cycle may be the norm rather than the exception [12,[37][38][39].…”
Section: Case Study Of Community Dynamics During Serial-dilution Cyclesmentioning
confidence: 99%
“…In our metabolic model, we only included acetate as the fermentation product due to its large excretion flux (49). There are of course other excretion products that can contribute to cell metabolism close to the colony surface where oxygen is available.…”
Section: Discussionmentioning
confidence: 99%